Adult education concepts in library professional development activities. Issue 5 (11th May 2015) - Attebury, Ramirose Ilene
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this review is to survey the literature addressing the professional development of academic librarians in the context of adult education principles. Design/methodology/approach – This article is a literature review. Findings – The review reveals that among those activities incorporating concepts from the adult education field andragogy, transformational learning, communities of practice and instructional design are most prevalent. Originality/value – To date, no other literature review considers adult education concepts in professional development of academic librarians.